2007
DOI: 10.1007/s00056-007-2606-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Occlusal Findings and Orofacial Myofunctional Status in Primary and Mixed Dentition

Abstract: Habitual open mouth posture (expressing hypotonia in the perioral muscles) and a visceral swallowing pattern become established during the primary dentition and are increasingly carried over into the mixed dentition period. Both criteria, along with assessment of occlusal relationships, are appropriate parameters with which to identify "children at risk for orthodontic treatment".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
0
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 27 publications
(68 reference statements)
5
76
0
26
Order By: Relevance
“…The frequency we assessed of sucking habits in primary dentition can be considered low. Stahl et al [15] reports 37% frequency of open mouth posture in primary dentition, which is comparable with our results. They also report prevalence of caudal and interdental tongue posture 21.4% and 12.5%, respectively, which is higher to our frequency rates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The frequency we assessed of sucking habits in primary dentition can be considered low. Stahl et al [15] reports 37% frequency of open mouth posture in primary dentition, which is comparable with our results. They also report prevalence of caudal and interdental tongue posture 21.4% and 12.5%, respectively, which is higher to our frequency rates.…”
Section: Discussionsupporting
confidence: 93%
“…They also report prevalence of caudal and interdental tongue posture 21.4% and 12.5%, respectively, which is higher to our frequency rates. Ovsenik et al [1] found 35% prevalence of atypical swallowing pattern, while Stahl et al [15] report 62% frequency in primary dentition. It is difficult to compare this study's re-ported prevalence of orofacial dysfunctions and oral habits with results of other studies due to their different study designs, functional parameters and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Orofacial functions were evaluated using the Nordic Orofacial Test-Screening (NOT-S) protocol, 11 translated and culturally adapted to Brazilian Portuguese.…”
Section: Orofacial Functionsmentioning
confidence: 99%
“…The CPQ [8][9][10] is composed of 29 questions and the CPQ 11-14 of 41. The minimum possible score is zero, and the maximum possible score is 116 for the CPQ [8][9][10] and 164 for the CPQ [11][12][13][14] .…”
Section: Orofacial Functionsmentioning
confidence: 99%
“…Ela inclui: ações vitais do organismo, como a respiração, a mastigação e a deglutição 2 ; postura muscular, como a postura dos lábios e língua 3,4 ; e atua como base para a interação social em relação à fala, para a comunicação emocional, à expressão facial e à aparência 2 . Desta forma, a disfunção orofacial pode ser severamente debilitante.…”
unclassified